On nonclassical boundary conditions for the contact of thin interlayers with different physical and mechanical properties on wave propagation in anisotropic media - Ispulov, N.A.; Qadir, Abdul; Zhumabekov, A.Zh.; Kurmanov, A.A.; Dosumbekov, K.R. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Wave processes are intensively studied in various fields of physics: electrodynamics, plasma physics, radiophysics, acoustics, hydrodynamics, etc. Along with the study of electromagnetic and elastic wave processes, the research of patterns of wave propagation of various physical nature in the presence of mutual transformation are of particular relevance. Wave processes in coupled fields reflect the mutual influence of elastic, electromagnetic and thermal fields. The coupling of electromagnetic fields to the deformation field takes place in a medium with piezoelectric, piezomagnetic and magnetostrictive properties. In the paper, based on the matrix method, the propagation of coupled elastic and electromagnetic waves in media with different physical and mechanical properties is studied. The paper proposes a generalization of non-classical contact conditions for studying the effect of thin layers with different physical and mechanical properties on wave processes. A system of differential equations of the 1st order with variable coefficients is constructed, which describe the propagation of electroelastic waves in anisotropic media of a rhombic system of class 222. The conditions for nonrigid contact for a thin layer with piezoelectric properties are derived. The possibility of studying layers with δ-shaped properties (δ is the Dirac function) is proved.
Анизотропты ортада толқындардың таралуы кезінде физика-механикалық қасиеттері әртүрлі жұқа қабаттардың классикалық емес шекаралық байланыс шарттары туралы
О неклассических граничных условиях контакта тонких прослоек с различными физико-механическими свойствами при распространении волн в анизотропных средах
Keywords: Maxwell’s equations; anisotropic medium; waves; non-rigid contact; matricant method